Regioselective Synthesis of Lactulose Esters by Candida antarctica and Thermomyces lanuginosus Lipases - Luis Chávez-Flores; Hiram Beltran; Daniel Arrieta-Baez; Dolores Reyes-Duarte (Catalysts, 2017)
The interest in sugar esters as emulsifiers has been increasing in recent years because they have tunable surfactant properties that depend on the chain length of the fatty acid and the type of the sugar, covering a wide range of hydrophilic-lipophilic balance (HLB). In this work, ten biocatalysts were used for the transesterification reaction screening of lactulose, a prebiotic sugar, with vinyl laurate. The reactions were followed by thin layer chromatography (TLC) analysis, identifying two major monoesters mixtures defined as monoester fraction 1 and monoester fraction 2. Candida antarctica lipase B (Novozym 435) produces “monoester fraction 1”, while Thermomyces lanuginosus lipase (Lipozyme® TL IM) and Mucor miehei lipase (Lipozyme®) seem to produce the same “monoester fraction 2”. These three enzymes were selected as model biocatalysts for a kinetic study, and monoester fractions 1 and 2 from Novozym 435 and Lipozyme® TL IM, respectively, were used for product characterization. Monoester fraction 1 contained 86.9% of the major monoester in position 1-O-, and monoester fraction 2 contained 91.4% of 6′-O-. Although these lipases acylated three positions of lactulose, they mainly synthesize a monoester presenting regioselectivity. These results contribute to the study of the chemical structure diversity of biosurfactants to enhance their applications in foods, pharmaceutical products, and cosmetics.